Case Open UEF – To do together - Hartikainen, Kaisa; Rissanen, Tuula (Septentrio Conference Series, 2017)
At the University of Eastern Finland (UEF) Library, the national Open Science and Research initiative (2014–2017, Ministry of Education and Culture of Finland) triggered the planning and construction of open science related research support services. Planning of support services with themes of open access scholarly publishing, open research data and open study material began at full throttle at the UEF Library in November 2015. Information specialists were grouped into teams, which orientated to separate aspects of open science and shared their knowledge by training the whole library staff. Teamwork continued actively over the year 2016. Open science continuously brings new tasks for the Library and has already notably changed the job profiles of the library specialists. Advancing open science has been considered highly important not only at the library but also at the university level. UEF has offered resources e.g. by recruiting new information specialists and a data protection officer and internal auditor. UEF Library has a vital role in conducting open science but it is practiced in close collaboration with University Services, especially that of Development Services, General Administration and Legal Services and IT Services. Open Science team has landed the departments to share information and to discuss about open science practices at UEF. Nowadays these roadshows concerning UEF publishing and data policy, open access (OA) publishing as well as research data management and sharing are our focal operation. Work continues but the results can already be seen: In the OA ranking of research organisations in Finland (Ministry of Education and Culture of Finland), UEF has achieved level four in the five-level maturity model. Also, UEF researchers can order tailored training sessions about open research and support services from the diverse training menu offered by the Library. Updated Open UEF web pages are available for everyone and multi-channeled informing directed to UEF staff and students continues online. One concrete output from conducted open science and active campaigning about self-archiving is UEF institutional publication repository, UEF//eRepository, which was launched in February 2017. At the moment about 31% of UEF scientific publications are open access, but substantial increase is expected. The next big challenge in open research is data management and opening. UEF Library is starting to build a metadata portal for research data in order to conceive the data produced by UEF researchers and to help finding data for potential reuse. Open science will also be included in information retrieval studies of master's degree and doctoral students. To encourage students and teachers in OA publishing, during the international open access week, one student publishing master's thesis openly will be rewarded with a stipend by the Library. Department having the highest rate of OA master's theses will also be adorned with flowers. Open science is a matter of teamwork, committing and keeping up to date.